2012
DOI: 10.1098/rstb.2012.0067
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the photosynthetic apparatus under fluctuating growth light

Abstract: Safe and efficient conversion of solar energy to metabolic energy by plants is based on tightly interregulated transfer of excitation energy, electrons and protons in the photosynthetic machinery according to the availability of light energy, as well as the needs and restrictions of metabolism itself. Plants have mechanisms to enhance the capture of energy when light is limited for growth and development. Also, when energy is in excess, the photosynthetic machinery slows down the electron transfer reactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 81 publications
2
88
0
1
Order By: Relevance
“…It is generally acknowledged that the PGRL1 protein participates to PSI-CEF both in C. reinhardtii and Arabidopsis (Arabidopsis thaliana; DalCorso et al, 2008;Iwai et al, 2010;Tolleter et al, 2011;Hertle et al, 2013;Johnson et al, 2014). By generating an additional proton motive force, PSI-CEF is proposed to enhance ATP synthesis in the illuminated chloroplast (Allen, 2003) and/or to trigger photoprotection of the photosynthetic apparatus (Joliot and Johnson, 2011;Tikkanen et al, 2012). Occurrence of PSI-CEF has been a matter of debate during the last decade, mainly because most experiments have been performed in nonphysiological conditions (e.g.…”
Section: Transitory Induction Of Pgrl1-dependent Psi-cef Upon Illuminmentioning
confidence: 99%
“…It is generally acknowledged that the PGRL1 protein participates to PSI-CEF both in C. reinhardtii and Arabidopsis (Arabidopsis thaliana; DalCorso et al, 2008;Iwai et al, 2010;Tolleter et al, 2011;Hertle et al, 2013;Johnson et al, 2014). By generating an additional proton motive force, PSI-CEF is proposed to enhance ATP synthesis in the illuminated chloroplast (Allen, 2003) and/or to trigger photoprotection of the photosynthetic apparatus (Joliot and Johnson, 2011;Tikkanen et al, 2012). Occurrence of PSI-CEF has been a matter of debate during the last decade, mainly because most experiments have been performed in nonphysiological conditions (e.g.…”
Section: Transitory Induction Of Pgrl1-dependent Psi-cef Upon Illuminmentioning
confidence: 99%
“…In fact, Tikkanen et al (2012) postulated that PSII photoinhibition is a major photoprotective mechanism because detached photoinhibited PSII centres and their LHCs slow down electron transfer, consequentially protecting PSI, which lacks an efficient repair system. This theory is supported by studies that found PSI damage was completely dependent on electron flow from PSII, as blocking LEF by 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) prevented PSI damage (Sonoike andTerashima, 1994, Havaux andDavaud, 1994).…”
Section: -5)mentioning
confidence: 99%
“…Tikkanen et al (2010) reason that the high dissipation capacity of qE under high light diminishes the need for qT. Under fluctuating light conditions, Tikkanen et al (2012) reported 'severely stunted phenotypes' in STN7-deficient mutants (stn7 and stn7stn8). The authors stated that "Coordination of excitation energy distribution between PSII and PSI from the common P-LHCII antenna is crucial in preventing the accumulation of electrons in ETC under low illumination phases of fluctuating growth light, and is therefore important for photoprotection of PSI in plant chloroplasts during the subsequent high light peak".…”
Section: State Transitions (Qt)mentioning
confidence: 99%
See 2 more Smart Citations